2018
DOI: 10.1002/stem.2897
|View full text |Cite
|
Sign up to set email alerts
|

c-MPL Is a Candidate Surface Marker and Confers Self-Renewal, Quiescence, Chemotherapy Resistance, and Leukemia Initiation Potential in Leukemia Stem Cells

Abstract: Acute myeloid leukemia (AML) is initiated and maintained by a unique, small subset of leukemia cells known as leukemia stem cells (LSCs). Self-renewal, quiescence, and chemotherapy resistance are key stemness properties of LSCs that are essential for poor clinical responses to conventional therapies. Identifying LSC surface markers and targeting LSCs are important for the development of potential therapies. In this study, application of chemotherapy treatment in AML-ETO9a (AE9a) leukemia mice led to the enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Concern has been raised in the use of thrombopoietin mimetic agents in MDS and AML patients, as c-MPL is also present on a considerable percentage of myeloid leukemia cells 30,31. Therefore, it is important to identify whether EP stimulates blast cells expressing c-MPL to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Concern has been raised in the use of thrombopoietin mimetic agents in MDS and AML patients, as c-MPL is also present on a considerable percentage of myeloid leukemia cells 30,31. Therefore, it is important to identify whether EP stimulates blast cells expressing c-MPL to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the high heterogeneity within and between patients, there is no single indicator to identify LSCs. Data have shown multiple candidate surface markers including CD123 ( 70 ), CD33 ( 71 ), CD96 ( 72 ), TIM-3 ( 73 ), CD44 ( 74 ), CLL-1 ( 75 ), c-MPL ( 76 ), MHDA2 ( 77 ), CD25 and CD32 ( 24 ) that play a significant role in the stemness properties of LSCs. Of these, CD25, CD32, CD123, c-MPL, and MHDA2 are expressed in quiescent human LSCs, and targeting these surface markers may facilitate the removal of dormant LSCs.…”
Section: Dormancy Of Lscs and Drug Resistancementioning
confidence: 99%
“…Since CD9 is hardly expressed on normal HSCs, it was suggested that this surface marker could be a promising new target for the eradication of LSCs. Second, AML cells positive for c-MPL, a thrombopoietin receptor regulating processes such as self-renewal and HSC proliferation, showed more chemoresistance than the c-MPL negative AML cell population in a mouse leukemic model [ 89 ] . Moreover, the c-MPL+ cells had a higher self-renewal potential and were significantly better at initiating AML in vivo compared to the c-MPL- cell population.…”
Section: Leukemic Stem Cell Targets In Acute Myeloid Leukemiamentioning
confidence: 99%